The Effect of Saint John Bosco's Educational System on the Caring end Educational Activity of Congregations in Poland - Alicja Puszka (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
The priest Saint Jan Bosco (1815-1888) was an eminent educator of the youth and the creator of an original educational system called a preventive one. John Bosco established a new congregation of Salesian brothers who took care of and educated the former juvenile prisoners as well as abandoned and orphaned boys from the neighbourhood of Turin. He entrusted a new congregation of Daughters of Mary Help of Christians (Salesian Sisters) with the task of taking care of poor and orphaned girls. The system was based on the principles of Christian education, on the Eucharistic life of the youth who were given wise love, friendship and goodness in the institutions and oratories. The youth attended vocational schools and workshops organized specially for them and those gave them a chance for a better life. Other religious orders concerned with educating children and youth in the Polish territories also draw from the Salesian educational models. These include Male and Female Congregations of Saint Michael the Archangel, Congregation of Sisters Shepherdesses of Divine Providence as well as lay associations within the so-called Salesian Family.